ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIK SISWA SMP DENGAN MENGGUNAKAN PENDEKATAN KONTEKSTUAL - Ditha Novianty Yolanda Abdullah; Luvy Sylviana Zanthy (Journal on Education, 2019)
This research is a qualitative descriptive study that aims to analyze the level of students' understanding ability by using a contextual approach in solving problems in set material by categorizing the level of high, medium, and low mathematical understanding abilities. The research subjects were 37-class VII-B students. The form of data collection is giving 4 items written test questions. Based on the results of the analysis, the average value of all instrument questions mathematical reasoning ability obtained, 69% for indicators of mechanical understanding which are characterized by activities of remembering and applying formulas routinely and counting simple, 52% for indicators applying formulas or concepts in simple cases or in similar cases, 56% for indicators prove the truth of a formula and theorem, and 97% for estimating the truth with certainty (without hesitation) before further analysis. so if it is totaled and averaged at 68%. Then the mathematical understanding ability of junior high school students in one of the seventh grade middle school in Cianjur is classified as moderate